Room-temperature superionic-phase nanocrystals synthesized with a twinned lattice - Jianxiao Gong (Nature Portfolio, 2019)
The ability to control the internal domain structure of a nanocrystal represents a new direction in nanomaterials design. Here, the authors develop a method to controllably introduce twin boundaries in cuprous sulfide nanocrystals, and find that twinning stabilizes these nanocrystals in the superionic phase well below room temperature.